Pendampingan dan Sosialisasi Protokol Kesehatan Covid-19 sebagai Upaya Persiapan Pembelajaran Tatap Muka - Dhananjaya Y.H. Kumarajati; Amalia Cemara Nur’Aidha; Bopi Yudha Sapa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
The Covid-19 pandemic has brought a significant impact on the world of education, including in Indonesia. In response, the Indonesian Ministry of Education and Culture issued Guidelines for the Implementation of Learning for the Second Semester of the 2020/2021 Academic Year during the Covid-19 Pandemic on November 20, 2020. SMK Kesehatan Binatama, an accredited